Vitamin B-Can it prevent cognitive decline? A systematic review and meta-analysis - Behrens, Annika; Grässel, Elmar; Pendergrass, Anna; Donath, Carolin (Systematic Reviews, 2020)
BACKGROUND: Development of cognitive decline represents substantial issues in today's society, steadily gaining importance with increasing life expectancy. One potential approach to preventing cognitive decline is to lower homocysteine by administering vitamin B. In this systematic review and meta-analysis, we address this topic and investigate whether oral supplementation of vitamin B can successfully prevent cognitive decline in cognitively unimpaired individuals. METHODS: A computerized systematic literature search was conducted using the electronic databases PubMed, Embase, and the Cochrane Library. Eligibility criteria included oral supplementation with vitamin B (B1, B6, folic acid, and B12) and the absence of cognitive impairment. A meta-analysis was conducted with "global cognition" as the primary outcome of this review. Secondary outcomes were changes in cognitive function in other cognitive domains reported in the included studies. Risk of bias was assessed according to the Cochrane Risk of Bias tool and the GRADE approach to establish the overall certainty of the evidence. RESULTS: The meta-analysis did not yield a significant overall effect of supplementation with vitamin B on cognitive function (Z = 0.87; p = 0.39; SMD, 0.02; 95% CI, - 0.034, 0.08). A sensitivity analysis focusing on specific risk factors did not alter this result. Some studies reported isolated significant effects of the intervention on secondary outcomes. However, these findings were outnumbered by the number of cognitive tests that did not yield significant effects. DISCUSSION: We found no overall evidence that oral vitamin B supplementation prevented cognitive decline. The isolated significant effects that were reported could be attributed to methodological issues. The results of this review do not provide evidence that population groups with certain risk factors would profit more from the intervention than others. Our findings do not apply to forms of administration other than oral supplementation nor do they offer information regarding the treatment of cognitively impaired individuals via the administration of vitamin B. SYSTEMATIC REVIEW REGISTRATION: PROSPERO CRD42017071692.
CRIS-Team Scopus Importer:2020-05-29
Keywords: Cognition[Mesh]; Dementia[Mesh]; Folic Acid[Mesh]; Prevention; Vitamin B12[Mesh]; Vitamin B6[Mesh]